Praktik Ziarah Kubur dan Perannya terhadap Hafalan Al-Quran di Makam KH. M. Munawwir Dongkelan, Panggungharjo, Bantul - Al-Ayyubi, M. Zia (MAGHZA: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This article aims to examine the influence of the practice of the grave pilgrimage to the tomb of KH. Munawir Krapyak on the memorization of students. Pilgrimage to KH. Munawir was not only done to visit the grave but to memorize the Qur'an. Using the living Qur'an theory, this article shows that the pilgrimage practice can have an impact on the recitation of the Qur'an. First, memorization tends to be easier and faster to enter the brain when compared to memorization, not in the tomb. Second, because KH. M. Munawwir is a religious symbol, he is seen as a supervisor who accompanies the process of memorizing the Al-Qur'an. Third, the continuity of the transmission of the sanad Al-Qur'an until it reaches the Prophet Muhammad